Implementation of Flipped Classroom Learning Model and Its Effect on Critical Thinking and Communicating Skills of Junior High School Students - Ratu Sampurna Ratu; Jodion Siburian; Agus Subagyo (Jurnal Penelitian Pendidikan IPA, 2025)
The 21st century learning paradigm emphasizes students' ability to think critically, be able to connect knowledge with the real world, master information technology, communicate and collaborate. This study aims to determine how the flipped classroom model affects students' critical thinking and communication skills. The research method is a quasi-experimental form of non-equivalent pretest-posttest control group design with a simple random sampling technique. The population in this study were all students of grade IX of SMP Islam Al-Falah, namely 5 classes, class IX-1, IX-2, IX-3, IX-4 and IX-5., the research sample class IX-5 as the control class and IX-3 as the experimental class. The data collection technique used the FRISCO indicator critical thinking ability essay test and the communication ability assessment observation sheet. The data analysis technique used the one-way MANCOVA test with initial critical thinking and communication skills as covariates. The results of the hypothesis test showed that the value [F (2,51) = 22.777, p <0.001, ηp2 = 0.472]. This means that the significance value of p <0.001 which means <0.05, then H0 is rejected and H1 is accepted, meaning that there is an influence of the flipped classroom model on students' critical thinking and communication skills. The size of the effect size value ηp2 = 0.472, which means that there is a large influence of the flipped classroom model on students' critical thinking and communication skills.